Audio-Magnetotelluric Modeling of Cimandiri Fault Zone at Cibeber, Cianjur - Handayani, Lina; Maryati, Maryati; Kamtono, Kamtono; Mukti, M. Ma’ruf; Sudrajat, Yayat (Geological Agency, 2017)
DOI: 10.17014/ijog.4.1.39-47The characteristic of Cimandiri Fault Zone has not been completely defined despite plenty of studies had already been accomplished. Therefore, an audio-magnetotelluric modeling was carried out. An audiomagnetotelluric survey was conducted at two parallel lines (N166oE) that intersected Cimandiri Fault Zone in Cibeber area, Cianjur. The distance between those two lines was 4.5 km and each line consisted of twenty-one stations with the distance between stations was 500 m. From the acquired forty-two apparent resistivity curves, inversion was executed to obtain two models. The models indicate layers with resistivity value of > 1000 ohm.m at about 500 m depth at both lines, which are associated to the basement layer. Columns of low resistivity zones in about the middle of each model represent fault zones as the weak zones of the area, and both models displayed them slightly dip southward as thrust faults.